KEKUATAN HUKUM AKTA JUAL BELI YANG DATANYA MERUPAKAN DATA PALSU (STUDI KASUS PUTUSAN PENGADILAN NEGERI DEPOK NOMOR 226/PDT.G/2018/PN.DPK) - Shela Oktaharyani Harahap; benny Djaja (Fakultas Hukum Universitas Tarumanagara, 2021)
PPAT has a very important role in land registration, namely helping the Head of Regency/Municipal BPN to carry out certain activities in land registration, but in practice there is falsification of data either carried out by an observer or other party. The problem faced is how the legal force of the sale and purchase deed whose data is false data based on the Depok District Court Decision Number 226/Pdt.G/2018/PN.Dpk; and how the PPAT is responsible for the sale and purchase deed which is declared null and void by the court. The research method used in this paper is a normative juridical research method. The results of the study indicate that there is actually a juridical defect in AJB No. 156/8/Sawangan/1997 dated July 28, 1997 made before Soekaimi, S.H., PPAT for the Bogor Regency area so that the deed does not meet the material requirements of an authentic deed and results in the cancellation of the deed by a court decision Regarding the PPAT's responsibility for the sale and purchase deed which is declared null and void by the court, of course there is a responsibility that must be carried out by a PPAT, be it administrative, civil, or criminal responsibilities.